Media Pembelajaran Berbasis Website Untuk Sekolah Menengah Atas Pada Pelajaran Teknologi Informasi Dan Komunikasi - Fakhruddin, Yusuf, Hernawan Sulistyanto, S.T.,M.T (2016)
Learning model currently applied at Senior High School 1 Sumber Lawang is conventional learning models. Students just listening content by teacher so the students easily bored and sleepy.The material presented are not acceptable to the fullest. This resulted in students not being able to understand the material submitted by teachers so that the value of some of the students were under the criteria of graduation is 70. This research aims to develop a web-based learning media on the subjects of Information and Communication Technology (ICT) Class X Senior High School 1 Sumber Lawang, Media-based learning website developed using HTML and PHP. The method is used by method of classroom action research. Data collected through the students learning outcomes achievement test. The students response data were collected through questionnaire. The collected data was then analyzed descriptively. The results of this study can be seen that the subject matter presented through the medium of web-based learning can improve students in Information and Communication Technology (ICT) as evidenced by the results of the exercise between conceptual learning and instructional media. The results of the exercise using of conventional learning showed the average value of the class is 69.5 while the average test results after using instructional media is 80.5.